Charlie Joe Jackson's guide to extra credit - Greenwald, Tom, 1962- (Roaring Brook Press, 2012)
Bright but unenthusiastic middle school student Charlie Joe Jackson signs up for the school play in an attempt to get straight As on his last quarter report card in order to avoid having to go to Camp Rituhbukkee over the summer.